Економічна стійкість – основа конкурентоспроможності підприємства - Бєлєнкова, О. Ю.; Антропов, Ю. В. (Ways to Improve Construction Efficiency, 2014)
The article considers theoretical approaches to the definition of "competitiveness" of sorts. It is alleged that the preservation of economic stability affects on the growth of competitiveness of enterprises